Board Characteristic and Shari’a Banks Performance: Evidence from Indonesia and Malaysia 2015-2020 - Aisyah, Siti; Umar Mai, Muhamad; Suhartanto, Dwi (Institut Agama Islam Negeri Madura, 2022)
This study aims to examine the effect of board characteristics on the performance of Islamic banks (IBs) in Indonesia and Malaysia in 2016-2020. The sample of this study includes 11 Islamic commercial banks in Indonesia and 7 Islamic commercial banks in Malaysia. The analysis method uses panel data regression which is processed with the help of software Eviews 12. Performance is measured by Return On Assets (ROA), Return On Equity (ROE), and Non-Performing Financing (NPF), Board characteristics are measured by the size of the board of directors, the proportion of directors women, the expertise of the board of directors, the size of the sharia supervisory board (DPS), the proportion of female DPS and the expertise of the DPS. The results of the study show that overall Islamic Corporate Governance and Corporate Governance have a positive effect on the performance of Islamic Banks (IBs). Keywords: Kata kunci: Islamic Banks; Islamic Corporate Governance; Corporate Governance; Performance Islamic Bank